A DNA vaccine based on hemagglutinin and conserved epitopes of influenza B virus provides cross-lineage protection in mice - Zhu, Xiangyu; Ha, Zhuo; Liu, Siyang; Zhang, He; Zhao, Wenxin; Qiu, Xiangshu; Cao, Xinyu; Wang, Wei; Xie, Yubiao; Shi, Ning; Han, Jicheng; Zheng, Wei; et al. (Frontiers in Immunology, 2025)
Conventional influenza vaccine can prevent infection and reduce the risk of post-infection complications. However, they lack the capacity to effectively respond to influenza virus mutations. This results in the vaccine becoming ineffective due to a reduced antigenic match. It is necessary to develop a new strategy for vaccine that will provide broad cross-reactive protection. A DNA vaccine based on the hemagglutinin (HA) gene and conserved antigenic epitopes of both the HA, M2e and NA genes to provide protection against influenza B was developed. BALB/c mice were immunized with electroporation to evaluate both humoral immune responses and T cell responses. Protection against influenza B virus challenge was evaluated in DNA vaccinated mice, followed by analysis of lung tissue to assess changes in cytokine levels and virus load. Additionally, various assays with DNA were conducted to assess their cellular uptake by DCs and their potential for immune activation. Vaccine via electroporation demonstrated the ability to enhance both humoral and cellular immune responses and resulted in the shaping of the immune response to the vaccine in a Th1 direction. Animals inoculated with vaccines via electroporation were completely protected against both homologous and heterologous viruses, as evidenced by the reduction of lung viral loads and lung inflammation, induction of broadly cross-protective humoral immunity, and IL-2 CD4+ T-cell responses. The most significant finding was that the DNA vaccine provided complete protection for mice against two distinct lineages of the lethal influenza B virus. These findings suggested that DNA vaccine delivered using in vivo electroporation effectively elicits a protective immune response and provides additional cross-protection.